On-line CE/ESI/MS interfacing: recent developments and applications in proteomics - Krenkova, Jana; Foret, Frantisek (Proteomics, 2012)
After shining as the ultimate separation - sequencing technique used for the successful completion of the Human Genome Project, in the early 2000s CE experienced lowered popularity among separation scientists. The renewed interest in recent years relates to the separation needs, especially in proteomics, metabolomics, and glycomics, where CE complements liquid chromatography techniques. This interest is further boosted by the regulators requiring additional separation techniques for characterization of newly developed pharmaceuticals. This paper gives a short overview of recent developments in the on-line interfacing of CE separation techniques with electrospray ionization/mass spectrometric analysis. Both the instrumentation and selected CE/ESI/MS applications including analyses of peptides, proteins, and glycans are discussed with the stress on research published in the past 3 years. Techniques related to the proteomic and glycomic analyses such as sample preconcentration, on-line protein digestion, and analyte derivatization prior CE/ESI/MS analysis are also included.
Keywords: Peptides; polysacharidy; hmotnostní spektrometrie s elektrosprejovou ionizací; Proteomics; lidé; peptidy; proteiny; proteomika; Electrophoresis, Capillary; Spectrometry, Mass, Electrospray Ionization; Polysaccharides; systémová integrace; elektroforéza kapilární; Systems Integration; Proteins; Humans